Pengaruh Word Of Mouth Dan Kualitas Pelayanan Terharap Loyalitas Pelanggan Dengan Kepuasan Konsumen Sebagai Variabel Intervening - Gunawan, Didik; Maharani, Suci; Layli, Devi (Management And Business Progress, 2024)
This research aims to determine the influence of Word of Mouth and Service Quality on Customer Loyalty with Consumer Satisfaction as an Intervening Variable (Case Study of JNE Customers, Tebing Tinggi Main Branch). This research used a sample of 96 respondents, namely JNE Tebing Tinggi Main Branch customers. This research uses quantitative research with the help of SmartPLS software version 3.0. The results of hypothesis testing using Hypothesis Testing (t Test) and Indirect Effect (Indirect Influence) to test the Intervening variable, researchers use Path Coefficients to test the hypothesis directly by producing the conclusion that hypothesis 1 is accepted, which means word of mouth has a significant effect on consumer satisfaction. hypothesis 2 is accepted, which means that service quality has a significant effect on customer satisfaction, hypothesis 3 is accepted, which means that word of mouth has a significant effect on customer loyalty, hypothesis 4 is accepted, which means that service quality has a significant effect on customer loyalty, hypothesis 5 is rejected, which means that consumer satisfaction has no significant effect. on customer loyalty, then the Indirect Effect test where hypothesis 6 is rejected, which means that consumer satisfaction cannot mediate the relationship between word of mouth and customer loyalty, hypothesis 7 is rejected, which means that consumer satisfaction cannot mediate the relationship between service quality and customer loyalty.